1999
DOI: 10.1212/wnl.53.7.1458
|View full text |Cite
|
Sign up to set email alerts
|

Critical decline in fine motor hand movements in human aging

Abstract: This technique sensitively detects age-related motor performance decline in humans. There may be a critical period in late midlife when fine motor performance decline either begins or abruptly worsens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
150
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(174 citation statements)
references
References 11 publications
21
150
1
2
Order By: Relevance
“…For instance, age-related declines in the speed of processing of visual stimuli in simple perception tasks have been reported in the literature [2]. In addition, a progressive slowing of arm movement speed according to task complexity has also been observed for older compared to young adults [22,44]. Finally, during aging, a decline in several aspects of proprioceptive sensitivity occurs [48] which certainly influences movement control.…”
Section: Overt Movement Executionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, age-related declines in the speed of processing of visual stimuli in simple perception tasks have been reported in the literature [2]. In addition, a progressive slowing of arm movement speed according to task complexity has also been observed for older compared to young adults [22,44]. Finally, during aging, a decline in several aspects of proprioceptive sensitivity occurs [48] which certainly influences movement control.…”
Section: Overt Movement Executionmentioning
confidence: 96%
“…Is this ability function of the kind and difficulty of motor task being imagined? It is well known that normal aging influences cognitive functions [2,13,24,40,41] and sensorimotor control of actions [22,43,44]. The state of musculoskeletal system, in particular that of muscular mechanics and structure, is also modified [17,23,26,32,46,47,49].…”
Section: Introductionmentioning
confidence: 99%
“…Some measures exhibit monotonic changes as a function of age, such as reductions in processing speed inferred from behavioral measures [6,58] and latency of certain brain potentials (P300) [21,27,46]. Other measures accelerate with increasing age, such as various tests of fluid intelligence [34], fine motor control [61] and possibly white matter integrity [44] cf. [1,64].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results, gender had a slight effect on the hand performance, but in some parts of the test, women performed better and faster than men [50]. On the other hand, in a study by Smith et al (1999), which was about the slight hand movement of the elderly, the results showed no difference between both the genders [51]. In another study, the mean score of PPT for senior men was 8.20, and for women, it was 3.20, which was the opposite of the findings of this study [52].…”
Section: Physical Trea Mentsmentioning
confidence: 92%